A review of the genus Solariola Flach, 1908 (Coleoptera: Curculionidae: Entiminae, Peritelini) - Baviera, Cosimo (Zootaxa, 2015)
The species of the Italian endemic weevil genus, Solariola Flach, 1908 (Coleoptera: Curculionidae: Entiminae), are revised, the genus is re-diagnosed, re-described and transferred from the tribe Otiorhynchini to Peritelini. Three new species are described: Solariola angelae n. sp. and Solariola pesarinii n. sp. from Sicily, and Solariola fraterna n. sp. from Calabria. Solariola hirtula (A. Solari & F. Solari, 1923) is considered a good species and not a subspecies of Solariola gestroi (A. Solari & F. Solari, 1904), bringing the total number of species considered valid to 9. All the previously described species are re-described in detail. Distribution, ecology, maps and figures are provided for all the species of the genus, as well as a species-level identification key and a checklist of all known species.